The Influence of Using Probiotic in Rations for Chicken Productivity - ., Gunawan; Sundari, M M S (Indonesian Animal Sciences Society, 2003)
The knowledge of probiotic spread widely, mainly after having been found some probiotics that can be used by animal. The result of research on the usage of some types of probiotics in rations of chicken give different influence on chicken productivity. Using probiotic starbio 0.25% in ration could increase the body weight of broiler up to 6 weeks of age and could increase the consumption of crude fibre up to 6% in the ration. Using probiotic starbio 0.25% in ration of layer could increase 19-26% eggs products and reduce feed conversion and water content in faeces and give additional income for the farmers as 44 up to 48%. Culture yeast as much as 0.2â0.3% is effective to add in rations of broiler 0â4 weeks of age. Lactobacillus acidophilus 2% and 4% in rations of layer may increase 5â11% of egg products and reduce feed conversion. It can be concluded that using probiotic in rations may increase the productivity of broiler, layer and native chickens. Â Key words: Probiotic, chicken diets, productivity of chicken